Reaksi Pasar atas Penyebaran Coronavirus Disease 2019 (COVID-19) - Putra, Alfian Nurwanto; Wijana Asmara Putra, I Nyoman (E-Jurnal Akuntansi, 2021)
COVID-19 has become a negative sentiment for stock markets around the world. On Monday, March 2, 2020, Indonesian President Joko Widodo announced the findings of the first COVID-19 infection case in Indonesia. This study aims to test whether there is a market reaction to the spread of COVID-19. Market reaction in this study is measured by abnormal returns, which is the difference between expected returns and realized returns. Abnormal returns in this study were estimated using a market-adjusted model. This study was conducted on issuers included in the LQ 45 index. The sample in this study was determined using purposive sampling technique. This research was conducted using March 2, 2020 and March 9, 2020 as the date of the event. The number of companies used in this study amounted to 45 companies. The results of this study indicate that on March 2 2020 there was no market reaction to the spread of COVID-19, while on March 9 2020 there was a market reaction to the spread of COVID-19. Keywords: Event Studies; Abnormal Return; COVID-19.